The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.7870/cjcmh-2008-0019
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Collaborative Mental Health Care Program in a Primary Care Setting: The Ottawa Share Program

Abstract: This article presents the results of a needs assessment of family physicians and residents concerning the provision of mental health care and an implementation evaluation of a multidisciplinary mental health service demonstration project, linking 2 family practices with mental health services of a general hospital. Family physicians and residents reported that collaborative mental health care provision would enhance but not replace their management of patients with mental health problems. The implementation ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Yet, many Canadians do not have access to psychotherapy due to the lack of support in the Canadian Medicare system and the high cost to access it in private practice settings (Hunsley, 2002;MHCC, 2012a;Myer & Payne, 2006;Vasiliadis, Tempier, Lesage, & Kates, 2009). One promising mental health care delivery method is interdisciplinary family health teams (FHTs), which may improve access to psychological services, while at the same time reduce costs (Mulvale, Danner, & Pasic, 2008;Swenson et al, 2008). St. Michael's Hospital and Ryerson University in Toronto developed a novel approach to provide marginalized populations with access to psychotherapy at no direct cost (Rouse, McShane, & Monson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, many Canadians do not have access to psychotherapy due to the lack of support in the Canadian Medicare system and the high cost to access it in private practice settings (Hunsley, 2002;MHCC, 2012a;Myer & Payne, 2006;Vasiliadis, Tempier, Lesage, & Kates, 2009). One promising mental health care delivery method is interdisciplinary family health teams (FHTs), which may improve access to psychological services, while at the same time reduce costs (Mulvale, Danner, & Pasic, 2008;Swenson et al, 2008). St. Michael's Hospital and Ryerson University in Toronto developed a novel approach to provide marginalized populations with access to psychotherapy at no direct cost (Rouse, McShane, & Monson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…And although there is research on collaboration between primary care physicians and mental health care providers (e.g. Kates, Crustolo, Farrar, & Nikolaou, 2002;Kates, 2008;Swenson et al, 2008), there is limited research on the provision of psychotherapy by clinical psychologists in a FHT setting save for a few (e.g. Chomienne at al., 2011;Cordeiro, Foroughe, & Mastorakos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This focus on restructuring arguably comes as a response to an increase in patient demand coupled with long wait times or inability to access psychiatric services. 1 These circumstances place increased responsibilities on family physicians to treat complex mental health conditions. 2 A lack of support for primary care providers to adequately and effectively treat mental health disorders sparked a shift toward collaborative models of care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing medication is an important aspect of evidence-based treatment for depression and anxiety [ 12 ]. However, FPs report moderate levels of comfort prescribing medications for these patients [ 13 ]. For example, Craven and Bland [ 14 ] who conducted a comprehensive literature review reported that PCPs are comfortable treating individuals with mental illness who are responsive to medication that the provider is familiar with prescribing.…”
Section: Introductionmentioning
confidence: 99%